Evaluating Brightness and Spectral Properties of Click Beetle and Firefly Luciferases Using Luciferin Analogues: Identification of Preferred Pairings of Luciferase and Substrate for In Vivo Bioluminescence Imaging - Zambito, Giorgia (Mol Imaging Biol, 2020)
PURPOSE: Currently, a variety of red and green beetle luciferase variants are available for bioluminescence imaging (BLI). In addition, new luciferin analogues providing longer wavelength luminescence have been developed that show promise for improved deep tissue imaging. However, a detailed assessment of these analogues (e.g., Akalumine-HCl, CycLuc1, and amino naphthyl luciferin (NH(2)-NpLH2)) combined with state of the art luciferases has not been performed. The aim of this study was to evaluate for the first time the in vivo brightness and spectral characteristics of firefly (Luc2), click beetle green (CBG99), click beetle red 2 (CBR2), and Akaluc luciferases when paired with different d-luciferin (d-LH2) analogues in vivo. PROCEDURES: Transduced human embryonic kidney (HEK 293T) cells expressing individual luciferases were analyzed both in vitro and in mice (via subcutaneous injection). Following introduction of the luciferins to cells or animals, the resulting bioluminescence signal and photon emission spectrum were acquired using a sensitive charge-coupled device (CCD) camera equipped with a series of band pass filters and spectral unmixing software. RESULTS: Our in vivo analysis resulted in four primary findings: (1) the best substrate for Luc2, CBG99, and CBR2 in terms of signal strength was d-luciferin; (2) the spectra for Luc2 and CBR2 were shifted to a longer wavelength when Akalumine-HCl was the substrate; (3) CBR2 gave the brightest signal with the near-infrared substrate, NH(2)-NpLH2; and (4) Akaluc was brighter when paired with either CycLuc1 or Akalumine-HCl when paired with d-LH2. CONCLUSION: We believe that the experimental results described here should provide valuable guidance to end users for choosing the correct luciferin/luciferase pairs for a variety of BLI applications. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s11307-020-01523-7) contains supplementary material, which is available to authorized users.